Analisis Faktor Penyebab Terjadinya Stress Pada Penderita Diabetes Melitus - Mahardika, Klara Vamiga Permata; Niken Anggreani; Nita Ashari; Sri Hartati; Elyandari, Wiwik Septerian; Retni; Tuti Rohani; Danur Azissah (Utami Publisher, 2025)
DM is the mother of all diseases. DM disease can spread everywhere. DM complications can arise from head to toe, ranging from heart disease and stroke and miserable kidney failure (Tandra, 2020). Poor blood sugar control affects the incidence of complications in DM. Factors that affect blood sugar levels in type 2 DM patients are divided into internal factors and external factors. External factors are age, gender, intake (carbohydrates, protein, fat, and fiber), physical activity, medication compliance, duration of DM, knowledge of DM and family support (Hayashino et al., 2017). The method used in this literature is a literature review. The method in this study uses sequential steps, namely: first, identification is carried out in advance that is appropriate for the research question, second, protocol development is carried out in the study, third, the location in the research database is determined as a search area, fourth, selecting relevant research results, fifth, sorting quality research results, sixth, extracting data from individual research, seventh, artificial results are carried out, eighth, presenting the results. Searching for articles is done through the use of online research journal databases. The results of the literature study indicate that the factors causing stress in people with diabetes mellitus consist of several causes such as age, duration of treatment, implementation of a strict diet, duration of healing when wounds, fear of complications. Other factors that also cause stress in people with diabetes mellitus are not being able to control themselves in dealing with problems in everyday life such as work, social environment and pressure in the family.